2020
DOI: 10.1002/jmrs.426
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound morphological patterns of testicular tumours, correlation with histopathology

Abstract: Introduction Ultrasound (US) plays a key role in the detection of testicular tumours. However, reliable characterisation of testicular tumours with US is difficult. The purpose of this study was to investigate the morphological patterns of testicular tumours as seen on modern US imaging and correlate these with histology. Methods The imaging features of 50 testicular tumours were analysed and compared with histology. The US appearance was categorized into 15 distinct morphological patterns. Results Patient’s a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…However, the average age of the patients in this research was 38.38+4.55 years. Likewise, Necas M et al [11] found that the patients were on average 39 years old. On the other hand, The average age of the patients was 30.95 years, according to Hamdan A et al [10].…”
Section: Discussionmentioning
confidence: 89%
“…However, the average age of the patients in this research was 38.38+4.55 years. Likewise, Necas M et al [11] found that the patients were on average 39 years old. On the other hand, The average age of the patients was 30.95 years, according to Hamdan A et al [10].…”
Section: Discussionmentioning
confidence: 89%
“…On B-mode ultrasound, seminomas present mostly hypoechogenic, sometimes lobulated and tend to be homogeneous compared to normal testicular tissue [ 15 , 16 ]. In contrast, most non-seminomas are rather inhomogeneous and show sometimes cystic structures and/or calcifications, which can be explained by more common tumor necrosis, mixed histologies and teratoma components [ 15 , 16 ]. Despite some distinct differences between seminomas and non-seminomas on ultrasound, no clear differentiation can be made preoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…What ‘was’ and what ‘is’ normal regarding testicular lesions is more related to their management, different for small (millimetric) and large nodules, and to the role of US in their evaluation, than to the capacity of US to definitively discover a malignancy and its histological type. In fact, US is still not accurate enough to define the origin of several lesions, and histology remains the only certain diagnostic tool 1,122,133–136 …”
Section: Standards In Scrotal Usmentioning
confidence: 99%
“…In fact, US is still not accurate enough to define the origin of several lesions, and histology remains the only certain diagnostic tool. 1,122,[133][134][135][136]…”
Section: Testicular Lesionsmentioning
confidence: 99%